Quality of life in children and adolescents with type 1 diabetes mellitus in HUSM - Nordin, Siti Nuraihan (2017)
INRODUCTION Type 1 diabetes mellitus (T1DM) is a chronic lifelong disease commonly diagnosed in children and adolescents. Factors that contribute to quality of life (QOL) outcome in T1DM patients were multivariable and remain controversial. A validated questionnaire translated to Bahasa Malaysia was used to measure QOL in children and adolescents with T1DM in Hospital Universiti Sains Malaysia (HUSM). The QOL assessment is important for better patient management as it allows identification of patients with difficulties who require early intervention. OBJECTIVES The aim of this study is to evaluate the QOL in children and adolescents with T1DM in HUSM, to determine factors associated with poor QOL in these patients and to determine correlation between QOL and metabolic control (HbA1c). PATIENTS AND METHODS A cross sectional study was conducted in children and adolescents with T1DM aged 10-18 years old attending follow-up in Paediatric Endocrinology Clinic, HUSM. The Malay translated version Diabetes Quality of Life for Youth (DQOLY) questionnaire were used using 5 Likert scales where low score indicate good QOL. Outcomes were analysed using Fisher’s Exact test, simple and multiple logistic regression analysis and Pearson correlation test.